(untitled) (World Economics and Finance Bulletin, 2024)
This article explores the significance of effective personnel management processes in ensuring public safety. It discusses the role of human resource practices in the recruitment, training, and retention of personnel responsible for public safety, including law enforcement, emergency services, and public health officials. The findings underscore the critical need for robust personnel management to enhance the effectiveness of public safety operations.